Comparative analysis of materials for retrograde filling, performed on distant teeth in liquid and dry environments (Эндодонтия Today, 2020)
In this study, a comparative analysis of materials for retrograde filling was carried out according to the criteria of usability, the degree of solidification and hermeticism in different environment. The study was performed on endodontically treated extracted teeth using the root filling materials, based on MTA: ProRoot MTA (Dentsply), Biodentine (Septodont), MTA HR Repair (Angelus), MTA grey (Angelus), BC sealer (Endosequence). After the retrograde root preparation and material packaging, all dents were divided in two groups for solidification in wet and dry environment. The quality of solidification and hermeticism was checked after 1 day. During the survey it was proved that some objects did not meet the requirements to the root filling materials which is used in the apical surgery. BC sealer (Endosequence), for example, is not suitable for long-term use and has a number of significant disadvantages. Among the selected materials, the most reliable are ProRoot (Dentsply) and Biodentine (Septodont). The usage of unidosis allows us to be ensured in sterility of the material; the ability to cure and preserve the hermeticism in the liquid conditions guarantees the density of the root canal obturation.